EFFECTIVENESS OF LIDOCAINE/PRILOCAINE CREAM ON PERCEIVED PAIN DURING MAMMOGRAPHY: A PILOT STUDY - Serife Simsek (International Journal of Surgery and Medicine, 2016)
Background: Mammography (MG) is an important imaging method in the diagnosis of breast diseases. However, pain during MG is an uncomfortable factor for the majority of women. Aim: The aim of this study is to determine the effectiveness of lidocaine/prilocaine cream on reducing pain during mammography. Methods: This is a prospective clinical study. A total of 60 female patients who had mammographic examination were equally divided into three groups; patients receiving 10 g EMLA cream (EMLA group), patients receiving 10 g Bepanthen cream (placebo group), and patients not receiving any cream (control group). Pain levels were assessed by using visual analogue scale (VAS) before and after MG. RESULTS: Each group was statistically similar in terms of basic patient characteristics. There was also no significant difference between the pre-MG VAS scores of the three groups (p = 0.996). On the other hand, VAS scores during MG was found significantly different between the groups (p = 0.001). When the groups were compared in pairs, the patients in EMLA group had significantly less post-MG VAS score than the Bepanthen and control groups (p = 0.001). There was no significant difference between Bepanthen and control groups (p = 0.678). CONCLUSION: To our knowledge, this is the first study demonstrating that a topical anaesthetic, EMLA, provides an effective analgesia during MG. Reducing the pain can change women’s preconceptions regarding MG.